Nurses’ Emotional Intelligence, Satisfaction in Lebanon: The Mediating Role of Job Stress - Al Kadi, Suzan; Beydoun, Abdul Rahman; Abbas, Alaa Elddine (International Review of Management and Marketing, 2023)
This study aims to examine the direct effect of nurses’ emotional intelligence (EI) on their job satisfaction, as well as the indirect effect through the mediating role of job stress (JS). The sample consisted of 365 nurses working in Lebanese hospitals during the COVID-19 period. The results revealed that EI elements (Self-awareness, self-management, social-awareness and relationship-management) had a significant positive effect on nurses’ job satisfaction. The existence of the negative mediation of job stress between the four EI skills and attitudes was found. The generalizability is limited to the Lebanese registered nurses in hospitals. Future research needs to incorporate other samples like the private nurses. A comparative study to provide further clarify the effect of EI and JS on the nurses at different levels is needed. This study extends research on organizational behavior to Eastern culture by examining the direct effect of EI on attitudes as well as the indirect effect through the mediating effect of JS which was not previously tackled. It suggests that the four skills of EI have a significant positive effect on nurses’ attitudes. It emphasizes the full mediation role of JS. The obtained results indicated that hospitals can increase job satisfaction bettering the employees’ EI.